THE IMPORTANCE OF INHALATION THERAPY IN THE INTENSIVE TREATMENT OF BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN (Herald of the National Children's Medical Center, 2025)
Broncho-obstructive syndrome (BOS) is manifested in children as a common clinical sign of acute respiratory tract diseases, characterized by inflammation of the bronchi, edema, and the accumulation of large amounts of sputum. This condition leads to acute respiratory failure and hypoxia. BOS is particularly common in children under the age of 3, which is associated with the anatomical and physiological features of their bodies. Improper treatment at home and the use of medications without medical advice can further worsen the condition.
Keywords: broncho-obstructive syndrome; children; inhalation therapy; intensive care; respiratory failure; hypoxia